Clinical observation on the treatment of displaced distal radial and ulnar fractures in children by closed manipulation combined with splinting - Wang, Guangwei; Huo, Liwei; Xu, Yidong; Dai, Gerong; Yang, Zhong; Hu, Jianwei; Liu, Weinian (Frontiers in Surgery, 2023)
Objective: To investigate the clinical efficacy of closed manipulation combined with splinting in the treatment of displaced distal radial and ulnar fractures in children. Methods: 82 children with displaced fractures of the distal radial and ulnar segment who met the inclusion criteria and were treated as outpatients or inpatients in orthopedic department of Guangzhou Orthopedic Hospital from January 2016 to June 2022 were randomly divided into an observation group and a control group. The 41 children in the observation group were treated with closed manipulation combined with splint fixation; the 41 children in the control group were fixed with incisional repositioning elastic nails combined with internal plates. The Anderson efficacy grading, VAS score, fracture healing time, treatment cost, hospital days, and complications were observed and compared between the two groups. Result: The efficacy was evaluated according to the Anderson forearm fracture efficacy evaluation criteria, and the results of statistical analysis showed no statistically significant differences between the two groups (P>0.05). At 3 weeks and 7 weeks after treatment, the VAS scores of children in both groups decreased (P<0.05), and the VAS scores in the observation group were significantly lower than those in the control group (P<0.05), indicating that the observation group had a significant advantage in the relief of pain after treatment. The fractures healed in both groups after treatment with the two different methods, and the difference in healing time between the two groups was not statistically significant (P > 0.05). The length of hospital stay, treatment cost and complication ratio were significantly lower in the observation group than in the control group (P < 0.05). Conclusion: In children with displaced fractures of the distal radial and ulnar segment, treatment by manual repositioning with external splinting can achieve satisfactory results with simple operation, low cost, short hospital stay and few complications, which is especially suitable to be promoted in primary hospitals and has good social benefits.